Managing multimedia semantics - Srinivasan, Uma, 1948-; Nepal, Surya, 1970- (Hershey PA : IRM Press, 2005)
'This book is aimed at researchers and practitioners involved in designing and managing complex multimedia information systems'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Multimedia systems